2006
DOI: 10.1002/14651858.cd003873.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for growth failure in childhood Crohn's disease

Abstract: In addition to these randomized controlled trials, a body of lower quality evidence does exist relevant to two other important interventions; the use of supplemental enteral nutrition (Morin 1980; Belli 1988; Israel 1995) and the judicious use of surgical interventions in pre-pubertal children with refractory disease (Alperstein 1985; Lipson 1990; McLain 1990). Newer treatments, such as infliximab, are now becoming more widely used and may offer advantages in promoting growth. These effects are as yet unstudie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 71 publications
0
15
0
1
Order By: Relevance
“…13 There is no universally accepted definition of growth failure or good evidence of how it should be treated. 40 Growth failure nevertheless remains a common problem, especially in paediatric Crohn's disease, and can persist into adult life. 41 There is also evidence from prospective paediatric studies that the growth failure is ''preprogrammed'', strongly suggesting a genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…13 There is no universally accepted definition of growth failure or good evidence of how it should be treated. 40 Growth failure nevertheless remains a common problem, especially in paediatric Crohn's disease, and can persist into adult life. 41 There is also evidence from prospective paediatric studies that the growth failure is ''preprogrammed'', strongly suggesting a genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concluded that despite the lack of large well-controlled studies, nutritional therapy is comparable to glucocorticoids in inducing remission and superior in improving height velocity 141 . Elemental and polymeric formulas were found equally effective in inducing remission.…”
Section: Part B Interventions and Practises For Maintaining And Imprmentioning
confidence: 99%
“…Contributing factors include reduced dietary intake as a result of reduced appetite, malabsorption and increased nutritional requirements associated with some diseases. Poor nutritional status and sub-optimal growth can have a detrimental effect on both short- and long-term disease outcomes (Corey 1988; CPS 1994; Koscik 2004). …”
Section: Introductionmentioning
confidence: 99%